ANALYSIS OF THE SOCIAL MEDIA USAGE ON THE DECISION TO THE ADMISSION OF NEW STUDENT PROCESS IN PRIVATE UNIVERSITY (Case Study: IBI Darmajaya Bandar Lampung) - Yan Aditiya Pratama; Anggalia Wibasuri; Lukman Hakim; Christina Christina (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Industrial revolution 4.0 has changed the business and people patterns on digital technology. This revolution is a cyber-physical system (CPS) that enables technology to bring virtual and physical worlds together in creating a connected internet-based world. Many companies must be able to transform themselves into the marketing company to compete globally. An important key in marketing is effective communication. This study determined the analysis of the usage impact of social media on the decision to the admission of new students in private universities. In this case, IBI Darmajaya Bandar Lampung was selected for this study in implementing the impact of social media usage for the marketing processes. This study was a qualitative approach with descriptive data processing from a survey conducted on student orientation in 2019. The selection of sampling in this study was a probability sampling design with a simple random sampling technique. The respondents were 100 new students. The results of this study were digital marketing using Whatsapp obtained at 95.8 per cent of the total respondents, Instagram at 92.8 per cent and Facebook users at 54.7 per cent. In addition, respondents obtained information about IBI Darmajaya 59 per cent from social media (WA, IG, FB, etc.) and the less was from others. It found that digital marketing approach impacted the marketing processes in this disruption era of marketing communication strategies on the admission of new students at IBI Darmajaya Bandar Lampung.Keywords: Digital Marketing, Social Media, Disruption 4.0, Customer Decision